PENERAPAN METODE THINK-PAIR-SHARE UNTUK MENINGKATKAN KEMAMPUAN PUBLIC SPEAKING SISWA DI SMA 2 UNGARAN - Dewi Rosnita Hardiani; Budiati Budiati; Maya Kurnia Dewi (Faculty of Economics, Law, and Humanities, 2019)
Public Speaking has a learning goal which is to form students' soft skills in communicatingin public. The way that can be used as a stimulus to improve students' communicationskills in public is to choose the right learning model that is Think-Pair-Share to beapplied in the learning process. The subjects of this study were 24 Language Classstudents at SMA N 2 Ungaran. The research procedure consists of two cycles coveringplanning, implementation, observation, and reﬂection. Data collection instruments arequestionnaires, skills assessment sheets, evaluation materials, and observation sheets ofstudent activities. The results of this study shows that in general, communication skills byapplying Think-Pair-Share or TPS models on public speaking topics are better for studentcommunication skills without using learning models. The application of the TPS learningmodel on the topic of public speaking is an effective learning model because it canimprove the communication skills of students of Language Class at SMA N 2 Ungaran.A signifcant increase in the public speaking ability of SMA N 2 Ungaran students wasfound in the indicators of ﬂuency in speaking and body posture of 0.68 points. While thelowest increase occurred in the indicator of material mastery that is 0.40 points.